Foreign Body Aspiration in Children-Diagnostic Clues through a Clinical Case - Elisabetta D'Addio; Pier Luigi Palma; Anna Di Sessa; Stefano Guarino; Pierluigi Marzuillo; Andrea Apicella (MDPI AG, 2022)
Foreign body aspiration is common in the pediatric age group, especially in males. Despite the high frequency of this potentially life-threatening event, it is not always easy to recognize it given the high variability of the clinical presentation and the potential of "pauci-symptomatic" inhalation. Moreover, a variable latency of the onset of symptoms since the moment of aspiration may be possible determining difficulties in the identification of the inhalation on an anamnestic basis. We describe the case of a 19-month-old boy who accessed the emergency room initially for a head trauma. The clinical evaluation, however, revealed an unexplained serious respiratory distress needing tracheal intubation. After our evaluation, we hypothesized that the severe respiratory distress determined an altered state of consciousness with following head trauma. The radiological findings raised the suspicion of foreign body aspiration for the presence of an atelectasis of the entire left lung. The computed tomography showed an abrupt interruption of the main bronchus at 12 mm from the hull. The following bronchoscopy identified an almond of 2 cm. We will review the literature to underline the diagnostic issues behind foreign body aspiration in children by highlighting the diagnostic clues that are helpful for emergency clinicians in the management of this condition.